The rate of stellar mass black hole scattering in galactic nuclei - Rasskazov, A; Kocsis, B (IOP Publishing, 2019)
We consider a black hole (BH) density cusp in a nuclear star cluster (NSC) hosting a supermassive back hole (SMBH) at its center. Assuming the stars and BHs inside the SMBH sphere of influence are mass-segregated, we calculate the number of BHs that sink into this region under the influence of dynamical friction. We find that the total number of BHs increases significantly in this region due to this process for lower-mass SMBHs by up to a factor of 5, but there is no increase in the vicinity of the highest mass SMBHs. Due to the high BH number density in the NSC, BH–BH binaries form during close approaches due to gravitational wind (GW) emission. We update the previous estimate of O'Leary et al. for the rate of such GW capture events by estimating the $\langle {n}^{2}\rangle /\langle n{\rangle }^{2}$ parameter where n is the number density. We find a BH merger rate for this channel to be in the range $\sim 0.002\mbox{--}0.04\,{\mathrm{Gpc}}^{-3}\,{\mathrm{yr}}^{-1}$. The total merger rate is dominated by the smallest galaxies hosting SMBHs, and the number of heaviest BHs in the NSC. It is also exponentially sensitive to the radial number density profile exponent, reaching $\gt 100\,{\mathrm{Gpc}}^{-3}\,{\mathrm{yr}}^{-1}$ when the BH mass function is ${m}^{-2.3}$ or shallower, and the heaviest BH radial number density is close to ${r}^{-3}$. Even if the rate is much lower than the range constrained by the current LIGO detections, the GW captures around SMBHs can be distinguished by their high eccentricity in the LIGO band.